Starije osobe i njihova percepcija prometa u gradu - Hinšt, Zlatko (Promet - Traffic&Transportation, 2012)
The paper discusses the results of the survey mounted in Zagreb in the summer of 1991 dealing with the perception of urban traffic by senior citizens. The survey involved 192 respondents, citizens of 55 years of age and above (traffic-related age criterion) and it served for obtaining the attitudes and opinions of senior citizens regarding some basic traffic problems of the Zagreb metropolitan area: assessment of public transport, urban traffic concept, and respective availability/ ease of access. Particular interest has been paid to the relationship of responses and respondents' characteristics (sex and 'mobility').